Functional MRI of the Olfactory System in Conscious Dogs - Jia, Hao; Pustovyy, Oleg M.; Waggoner, Paul; Beyers, Ronald J.; Schumacher, John; Wildey, Chester; Barrett, Jay; Morrison, Edward; Salibi, Nouha; Denney, Thomas S.; Vodyanoy, Vitaly J.; Deshpande, Gopikrishna (PLOS ONE, 2014)
We depend upon the olfactory abilities of dogs for critical tasks such as detecting bombs, landmines, other hazardous chemicals and illicit substances. Hence, a mechanistic understanding of the olfactory system in dogs is of great scientific interest. Previous studies explored this aspect at the cellular and behavior levels; however, the cognitive-level neural substrates linking them have never been explored. This is critical given the fact that behavior is driven by filtered sensory representations in higher order cognitive areas rather than the raw odor maps of the olfactory bulb. Since sedated dogs cannot sniff, we investigated this using functional magnetic resonance imaging of conscious dogs. We addressed the technical challenges of head motion using a two pronged strategy of behavioral training to keep dogs' head as still as possible and a single camera optical head motion tracking system to account for residual jerky movements. We built a custom computer-controlled odorant delivery system which was synchronized with image acquisition, allowing the investigation of brain regions activated by odors. The olfactory bulb and piriform lobes were commonly activated in both awake and anesthetized dogs, while the frontal cortex was activated mainly in conscious dogs. Comparison of responses to low and high odor intensity showed differences in either the strength or spatial extent of activation in the olfactory bulb, piriform lobes, cerebellum, and frontal cortex. Our results demonstrate the viability of the proposed method for functional imaging of the olfactory system in conscious dogs. This could potentially open up a new field of research in detector dog technology.